2020
DOI: 10.1002/2688-8319.12031
|View full text |Cite
|
Sign up to set email alerts
|

Examining assumptions of soil microbial ecology in the monitoring of ecological restoration

Abstract: 1. Global interest in building healthy soils combined with new DNA sequencing technologies has led to the generation of a vast amount of soil microbial community (SMC) data. 2. SMC analysis is being adopted widely for monitoring ecological restoration trajectories. However, despite the large and growing quantity of soil microbial data, it remains unclear how these data inform and best guide restoration practice. 3. Here, we examine assumptions around SMC as a tool for guiding ecosystem restoration and evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 110 publications
1
16
0
Order By: Relevance
“…However, the soil microbiome is extremely complex because of its large taxonomic diversity and entangled biogeochemical processes (Fierer, 2017). The large number of microbial species, processes and their interactions has resulted in large uncertainties regarding predicted ecosystem services and restoration outcomes (Hart et al., 2020; Schimel & Schaeffer, 2012). For instance, a recent meta‐analysis found that including microbial taxonomic composition, in addition to environmental variables, as predictors of carbon and nitrogen process rates only improved predictive power by ~10% on average (Graham et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, the soil microbiome is extremely complex because of its large taxonomic diversity and entangled biogeochemical processes (Fierer, 2017). The large number of microbial species, processes and their interactions has resulted in large uncertainties regarding predicted ecosystem services and restoration outcomes (Hart et al., 2020; Schimel & Schaeffer, 2012). For instance, a recent meta‐analysis found that including microbial taxonomic composition, in addition to environmental variables, as predictors of carbon and nitrogen process rates only improved predictive power by ~10% on average (Graham et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our approach provides a new opportunity to infer the continuous distribution of soil fungal community at a large area with the less sampling density and consequently less laboratory analysis costs. The approach will complement molecular approaches for the assessment, characterization and improved understanding of soil fungal communities and their associated functions at different scales (Hart et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…postglacial; Napier et al, 2019). Overall, next generation sequencing has the potential to uncover long overlooked interactions and unseen diversity, with significant implications for ecosystem restoration and conservation (Williams et al, 2014; but see Hart et al, 2020).…”
Section: New Horizons and Types Of Data For The Fieldmentioning
confidence: 99%